ادارہ تحقیقات اسلامی کی فقہ پر مطبوعات: ایک جائزہ .................................................................................. The Books of Islamic Research Institute on Islamic Law - بشیر ثمینہ (FIKR-O NAZAR فکر ونظر, 2018)
Islamic Research Institute (IRI) has been serving the Muslim Ummah in multiple ways, among those its publications have been embraced and appreciated widely. This article presents the review of different works on Islamic Law published by IRI. It begains with an introduction of fiqh and a short history of its compilation. It has discussed the nature, value, importance and usefulness of these works, while also pointed out some weaknesses (which are very few of course). The books published by IRI on Islamic Law are in English, Urdu and Arabic. Some of these books have been chosen for this article. Hopefully it will provide a glimpse to the reader of these works and encourage him/her to benefit from these publications.